A Critical Study of Community Aspirations on the Formation of a Sharia BPR Regional-Owned Enterprise (BUMD) in the Regional Work Plan of Serang City - Jamas, Irkham Magfuri; Said, Syihabudin; Rudjikartawi, Erdi; Abduh, Muhammad (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Islamic economics as an alternative solution to the socialist and capitalist economic systems that have failed to provide economic welfare in the world. Islamic economics needs to be implemented, especially in areas inhabited by a Muslim majority. Serang City, with a predominantly Muslim population, is an ideal place for the implementation of Islamic economics. The community's need for halal financing alternatives has become an issue that needs to be addressed together by both the community and local government. This relatively new study aims to analyze the aspirations of the community regarding the formation of a Sharia BPR Regional Owned Enterprise (BUMD) in Serang City within the regional work plan. This study uses a descriptive qualitative method with data collection through observation, questionnaires, and interviews. The results indicate that based on the community's aspirations gathered through channels such as student organizations, religious organizations, academics, and community leaders, it was found that the people of Serang City expressed the need for the establishment of a Sharia BPR BUMD in Serang City, given the needs and rights of the Muslim community in Serang City in particular, as well as the spirit of moving away from usury, which needs to be facilitated. Therefore, this study recommends the formation of a Sharia BPR BUMD in Serang City.